Complicaciones y tratamiento de las fracturas supracondíleas de húmero en la infancia - Ruilova Maldonado, María José (Machala: Universidad Técnica de Machala, 2023)
Introduction: Supracondylar fractures of the humerus, are caused by the solution of continuity of the distal metaphysis of the humerus, above the condyles; it is the most common fracture around the elbow affecting most frequently children between the ages of 5 to 7 years, they are classified into four types according to the degree of complexity, although most are simple fractures with good prognosis complications may occur that vary according to the time in which treatment is instituted therefore the urgency of immediate attention lies in the prevention of complications and sequelae. Objective: to describe the complications and treatment of supracondylar humerus fractures in childhood by means of an updated bibliographic review. Methodology: a systematic review with a descriptive, qualitative and cross-sectional approach was performed by searching highly specialized databases of updated scientific articles from the last 5 years. Conclusions: The most frequent complications were neurological being most commonly affected the median nerve, vascular complications and ulnar varus, in less frequency are myositis ossificans, avascular necrosis of the trochlea and infections. On the other hand, the modified Gartland classification allows to guide the physician on the most appropriate management depending on the type of fracture, from a conservative management applied in grades I and II, to surgical management in the case of more complex fractures such as those of grade III and IV.
Introducción: Las fracturas supracondíleas de húmero, son ocasionadas por la solución de continuidad de la metáfisis distal del húmero, por encima de los cóndilos; es la fractura más común alrededor del codo afectando con mayor frecuencia a niños entre las edades de 5 a 7 años, se clasifican en cuatro tipos según el grado de complejidad, aunque la mayoría son fracturas simples con buen pronóstico pueden presentarse complicaciones que varían de acuerdo al tiempo en que se instaura el tratamiento por lo tanto la urgencia de una atención inmediata radica en la prevención de complicaciones y secuelas. Objetivo: describir las complicaciones y el tratamiento de las fracturas supracondíleas de húmero en la infancia mediante una revisión bibliográfica actualizada. Metodología: se realizó una revisión sistemática con enfoque descriptivo, cualitativo y transversal, mediante la búsqueda en bases de datos altamente especializados de artículos científicos actualizados de los últimos 5 años. Conclusiones: Las complicaciones más frecuentes fueron las neurológicas siendo más comúnmente afectado el nervio mediano, las complicaciones vasculares y el cúbito varo, en menor frecuencia están la miositis osificante, la necrosis avascular de la tróclea e infecciones. Por otro lado, la clasificación de Gartland modificada permite orientar al médico sobre el manejo más adecuado dependiendo del tipo de fractura, desde un manejo conservador que se aplica en los grados I y II, hasta el manejo quirúrgico en el caso de fracturas más complejas como son aquellas de grado III y IV.
Keywords: FRACTURAS; SUPRACONDILEAS; COMPLICACIONES; NIÑOS